2011
DOI: 10.1093/ageing/afr020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of management of oral anticoagulation as assessed by time in therapeutic INR range in elderly and younger patients with low mean years of formal education: a prospective cohort study

Abstract: good-quality management of oral anticoagulation is achievable in deprived populations attending an anticoagulation clinic. Elderly patients may experience similar quality of anticoagulation despite having higher levels of co-morbidities and polypharmacy. These results add evidence to the safety of such therapeutic interventions in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…This is an important finding as the prevalence of AF increases with age [1] and [14]. Costa et al [10] also found that elderly patients achieved a good quality of VKAs anticoagulation despite having a higher levels of comorbidities and polypharmacy. In the Swedish national quality registry for atrial fibrillation and anticoagulation (AuricuLA) [11] a correlation between age and major bleeding was found, but no correlation was seen between age and thrombo-embolic events.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is an important finding as the prevalence of AF increases with age [1] and [14]. Costa et al [10] also found that elderly patients achieved a good quality of VKAs anticoagulation despite having a higher levels of comorbidities and polypharmacy. In the Swedish national quality registry for atrial fibrillation and anticoagulation (AuricuLA) [11] a correlation between age and major bleeding was found, but no correlation was seen between age and thrombo-embolic events.…”
Section: Discussionmentioning
confidence: 84%
“…Although AF prevalence increases with age [1] previous data show a high rate of inappropriate anticoagulation among octogenarians with AF [8] and [9], however the data reported in the last five years suggest that this might be changing [10] and [11].Our aim was to study the clinical profile of octogenarians who receive oral anticoagulation due to nonvalvular AF and to study the effect of age on the quality of VKAs anticoagulation assessed by TTR.…”
Section: Introductionmentioning
confidence: 98%
“…One study analyzed data from individuals aged 65 and older (mean age 82) with AF treated at an urban academic geriatrics practice over a 1-year period and found a TTR of 49%. 28 Another study also found a lower TTR in elderly adults, compared to younger counterparts (29) whereas two other studies (30,31) found that elderly adults achieved a good quality of anticoagulation, assessed by TTR, despite having more comorbidities and greater polypharmacy. The Swedish national quality registry for AF also revealed that elderly adults manage their warfarin therapy as well as or better than younger individuals.…”
Section: Discussionmentioning
confidence: 98%
“…The usual international normalised target (INR) of 2.0-3.0 which optimises the efficacy and safety of warfarin therapy is difficult to achieve consistently especially among older adult patients due to prevalence of factors such as polypharmacy and comorbidity as discussed in the previous section [10][11]. Even in presence of simple, safe, and accurate warfarin regimen [12], maintaining people on warfarin therapy is a complex process and may lead to incompliance and possible instability of anticoagulation levels [13]. Therefore, warfarin therapy requires regular monitoring of the INR, regardless of age, to ensure its effectiveness and safety.…”
Section: Vitamin K Antagonistsmentioning
confidence: 99%